Increased SCF in Follicular Fluid and Granulosa Cells Positively Correlates With Oocyte Maturation, Fertilization, and Embryo Quality in Humans. (November 2017) - Tan, Jun; Zou, Yang; Wu, Xing-Wu; Tian, Li-Feng; Su, Qiong; He, Jin-Xia; Huang, Zhi-Hui; Zhao, Yan; Wu, Li-Ping; Wu, Qiong-Fang
Stem cell factor (SCF), which is derived from granulosa cells (GCs), plays a key role in the process of follicular development and oocyte maturation. The present study aimed to explore whether the levels of SCF in follicular fluid (FF) and GCs can be used as a potential marker for predicting oocyte developmental potential. Follicular fluid and GC samples from 150 female patients undergoing intracytoplasmic sperm injection were collected in this study. The SCF concentrations in FFs and SCF messenger RNA (mRNA) in GCs were evaluated by using enzyme-linked immunosorbent assay and real-time polymerase chain reaction, respectively. The results showed that the levels of SCF protein and mRNA were significantly associated with oocyte maturation, normal fertilization, cleavage, and embryo quality. Moreover, the levels of SCF protein and mRNA in pregnancy group were also higher than those in the nonpregnancy group. The cutoff value of SCF in FF for predicting high-quality embryo was 1.346, with a sensitivity of 57.8% and a specificity of 72.4%, and the cutoff value of SCF in GCs for predicting high-quality embryo was 6.650, with a sensitivity of 64.4% and a specificity of 78.1%. In conclusion, our results showed a positive and statistically significant relationship between SCF level and oocyte maturation, normal fertilization, cleavage, embryo quality, and clinical pregnancy. Therefore, the levels of SCF in FF and GCs might be considered as a new marker for predicting oocyte developmental potential.